A nonparametric frontier measure of marketing efficiency: An illustration with corn ethanol plants. Issue 3 (18th December 2017) - Sesmero, Juan; Perrin, Richard; Fulginiti, Lilyan
Abstract: This article extends nonparametric measures of efficiency to accommodate the concept of marketing efficiency, which measures changes in net revenues brought about by firms' use of marketing channels other than spot markets. The measure is appropriate for firms operating under atomistic competition with imperfect information. The proposed measure displays two important features: (a) it uses the alternative of a spot price‐based counterfactual to distinguish marketing from allocative efficiency, and (b) it allows for the fact that firms operate in different spot markets and have access to diverse sets of prices. We illustrate this approach with a unique dataset from ethanol plants in the U.S. Corn Belt. [EconLit citations: C61, D2, L2].